CARDIOPROTECTIVE EFFECTS OF ETHANOLIC LEAF EXTRACT OF IPOMOEA BATATAS ON DOXORUBICIN INDUCED CARDIOTOXICITY IN RATS - Somashekar, Balakrishna; Rai, Shiva Shanker; Gowda Kp, Shivalinge (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: This study was aimed to investigate the protective effects of ethanolic leaf extract of Ipomoea batatas (EEIB) on doxorubicin (DOX) induced cardiotoxicity using Albino Wistar rats by monitoring the enzymatic, non-enzymatic antioxidant levels, serum enzyme levels, microscopical examinations and the study in electrocardiography (ECG) alterations. Methods: The rats were treated with EEIB (300, 600, 900 mg/kg body weight, n=6) and vitamin C (50 mg/kg) orally for 10 days and the rats were also treated with DOX 15 mg/kg on 7th day. On the 11th day, the rats were treated with anaesthetized with anesthetic ether, ECG and the levels of biochemical and histological observations of the heart tissues were performed. Results: The levels of cardiac markers like creatinine kinase (CK-MB), CK, lactate dehydrogenase and lipid peroxides were significantly decreased in the extract (600, 900 mg/kg) and ascorbic acid pretreated rats when compared to DOX with significance p<0.001. In heart superoxide dismutase, catalase, tissue protein and glutathione levels were significantly increased in the extract (600, 900 mg/kg) and ascorbic acid pretreated rats when compared to DOX with significance of p<0.001. The heart weight and electrographic alterations were gradually recovered by the extract in a dosedependent manner. There was no significant recovery of the above-mentioned parameters with an extract dose of 300 mg/kg. Conclusion: The study revealed that the extract and vitamin C have a dose-dependent potential to prevent oxidative damage/free radical damage induced by DOX in heart. Keywords: Doxorubicin, Vitamin C, Ipomoea batatas, Serum enzymes, Antioxidant enzymes. Â 